HUBUNGAN IKLIM ORGANISASI, EUSTRESS DENGAN KINERJA KARYAWAN DI PT. PULSA INDOMEDIA PRATAMA - Rosalina Ayudia; Teddy Rochendi (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2020)
Aim of this study is to describe the direct effect of these particular points: 1). The atmosphere of the organization on employee performance. 2). Eustress on employee performance. . What we need to know in this study is which of these free variables will be dominant to affect employee performance at PT. Pulsa Indomedia Pratama. This thesis is using quantitative method. Whereas data analytic methods used in this thesis are parametric analysis via linear regression analysis and hypothesis testing via T-Test and F Anova Test. Data were collected from two different sources, primary and secondary sources. Data from the primary source were collected from a questionnaire, distributed to 42 respondents. The questionnaire consists of all variables that have been studied. In another hand, data from the secondary source were obtained from textbooks and literature, and other information regarding the study from an insider of the company. This researchable to provide information about which factors and how these factors affect the performance of employees. So it can be recommended for the leadership to take the best strategy for improving employee performance